2017
DOI: 10.1186/s12943-017-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum HOTAIR as a novel diagnostic biomarker for esophageal squamous cell carcinoma

Abstract: BackgroundEarly diagnosis of esophageal squamous cell carcinoma (ESCC) is an important issue to improve the prognosis. HOX transcript antisense RNA (HOTAIR), a long noncoding RNA (lncRNA) expressed from the HOXC locus, has been recently revealed as an oncogenic regulator in ESCC. This study aimed to investigate whether serum HOTAIR is involved in the diagnosis of ESCC.MethodsIn this study, we detected serum HOTAIR expression in 50 patients with ESCC (including 42 tumor resection and 8 without surgery) and 20 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 29 publications
0
74
0
Order By: Relevance
“…LncRNAs, especially circulating ones, are stable and accessible and are considered potential diagnostic or prognostic markers in some types of cancer [24-26]. Clinically, overexpression of LncDQ has been observed in active CD and correlates with disease severity [15].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs, especially circulating ones, are stable and accessible and are considered potential diagnostic or prognostic markers in some types of cancer [24-26]. Clinically, overexpression of LncDQ has been observed in active CD and correlates with disease severity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Long non‐coding RNAs are a family of RNAs that have no coding capacity however still exhibit the ability to play a crucial role in various biological regulatory processes such as a performance as a competing endogenous RNA (ceRNA) influencing post‐transcriptional regulation by interfering the pathways of microRNA (miRNA or miR) . A previous study revealed the diagnostic potential of serum lncRNA HOX transcript antisense RNA (HOTAIR) as a promising biomarker for oesophageal squamous cell carcinoma . HOTAIR is a 2148‐nucleotide‐long lncRNA that has been shown to participate in the development of the physiological epidermis as well as the progression of cancer, and potentially as a regulator of tumour suppressor genes .…”
Section: Introductionmentioning
confidence: 99%
“…10 A previous study revealed the diagnostic potential of serum lncRNA HOX transcript antisense RNA (HOTAIR) as a promising biomarker for oesophageal squamous cell carcinoma. 11 HOTAIR is a 2148-nucleotide-long lncRNA that has been shown to participate in the development of the physiological epidermis as well as the progression of cancer, and potentially as a regulator of tumour suppressor genes. 12 Apart from lncRNA, accumulating evidence has highlighted the crucial inhibitory role of miRs in blocking the development of oesophageal cancer, such as microRNA-204 (miR-204), which performs as a tumour suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA is a class of transcript with more than 200 nucleotides in length, but do not encode proteins . Aberrant expressions of lncRNAs have been revealed in various pathological status, particular in cancers . Furthermore, lncRNAs also play important roles in various pathophysiological processes, including cancers .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Aberrant expressions of lncRNAs have been revealed in various pathological status, particular in cancers. [10][11][12][13] Furthermore, lncRNAs also play important roles in various pathophysiological processes, including cancers. [14][15][16][17][18] In NSCLC, several lncRNAs are reported to participate in tumourigenesis and/or development of NSCLC.…”
mentioning
confidence: 99%